Psychosocial work characteristics and demographic variables as predictors of burnout/engagement of basic education teachers - RAMONA ISABEL, JOSE (Archīum Ateneo, 2014)
This study attempted to identify the profile of demographic variables, psychosocial work characteristics, and burnout/engagement of faculty members of a Catholic coeducational private school in Muntinlupa for school year 2013-2014, as perceived by themsel